Assessing the differentiated contribution of city resources to city brand image - José Antonio Folgado-Fernández; Paulo Alexandre Oliveira Duarte; José Manuel Hernández-Mogollón (Tourism & Management Studies)
Intense competition among tourism destinations has forced tourism managers to use all their available resources in comprehensive strategies to improve their place image, including city managers who are looking to create a distinctive, strong city brand image capable of attracting tourists. The main objective of this paper is to assess the contribution of cultural heritage, events, tourist attractions and infrastructure to the development of cities’ brand image. A sample of Spanish tourists who visited the Spanish town of Plasencia was used to assess the contribution of these factors to city brand image development through partial least squares path modelling. The results show a significant, but differentiated, contribution of the four factors to city brand image, with events offering the lowest contribution. The findings provide tourism managers with new insights into how best to use each resource to build a strong city brand image and improve marketing strategies for their cities.